Simulation of Hybrid Mesh Turbomachinery using CFD and Additive Technologies - Yuri A. Sazonov; Mikhail A. Mokhov; Inna V. Gryaznova; Victoria V. Voronova; Khoren A. Tumanyan; Mikhail A. Frankov; Nikolay N. Balaka (Salehan Institute of Higher Education, 2022)
This paper develops schematics and evaluates the performance of hybrid mesh turbomachinery at the patenting stage of individual technical solutions. This type of turbomachine uses reduced-sized blades and also forms flow channels with a mesh structure between the blades. The research methods are based on simulations using computational fluid dynamics (CFD) and additive technologies. An intermediate conclusion is that a new scientific direction for investigating and creating hybrid mesh turbomachinery equipped with mesh jet control systems was formed to develop Euler's ideas. This paper describes new possibilities for the simultaneous implementation of two workflows in a single impeller: 1) Turbine workflow, and 2) Compressor workflow. Calculation methods showed possible improvements in the performance of the new turbomachines. This paper considers options for mesh turbomachine operation in the two-stage gas generator mode with partial involvement of atmospheric air in the workflow. Preliminary calculations based on examples show that it is possible to expect a two- to four-times increase in thrust when using hybrid mesh turbomachines. Ongoing studies mainly focus on developing multi-mode turbomachinery that works in complicated conditions, such as offshore oil and gas fields, but some research results are applicable in other industries, for example, in developing hybrid propulsion systems or propulsors. Doi: 10.28991/CEJ-2022-08-12-011 Full Text: PDF